The impact of anesthesia clerkship training on procedural timing: a focus on medical students in anesthesiology - Chatmongkolchart, Sunisa; Saetang, Mantana; Kunapaisal, Thitikan; Yongsata, Dararat; Saelim, Kantaros (Frontiers in Education, 2024)
The impact of medical student involvement in anesthetic procedures on operating room (OR) efficiency and patient outcomes remains understudied, despite its importance in medical education. This study aimed to quantify the effects of fifth-year medical students' participation in anesthetic procedures on key time metrics, perceived difficulty, procedural success, and postoperative complications and to compare these effects with those of anesthetic residents and student nurse anesthetists.Methods: This prospective observational study was conducted between April and July 2022 in the OR of a tertiary university hospital in southern Thailand. We analyzed 111 elective obstetricgynecologic and general surgery procedures under subarachnoid block or general anesthesia, equally distributed among three groups: fifth-year medical students, anesthetic residents, and student nurse anesthetists. Key time intervals, perceived difficulty, number of attempts, success rates, and postoperative complications were recorded and compared across groups.Results: Fifth-year medical students exhibited significantly prolonged anesthesia release time, anesthesia-controlled time, anesthetic preparation time, and anesthetic procedure time compared to anesthetic residents and student nurse anesthetists (p < 0.05). Medical students perceived case inductions as more challenging than the other groups did (p < 0.001), but procedural success rates were comparable across groups. Immediate postoperative airway complications were more frequent among medical students than anesthetic residents, but no significant differences were found in intraoperative or 24-hour postoperative complications. Discussion: While the involvement of medical students in anesthetic procedures extends specific time metrics, it does not significantly impact overall case duration or major patient outcomes. These findings support the continued integration of medical student training in the OR, with appropriate supervision to manage the slightly increased risk of immediate postoperative complications. Further research is needed to optimize the balance between educational opportunities and OR efficiency.